Capmatinib in Japanese patients with MET exon 14 skipping–mutated or MET‐amplified advanced NSCLC: GEOMETRY mono‐1 study. Issue 4 (24th February 2021) - Seto, Takashi; Ohashi, Kadoaki; Sugawara, Shunichi; Nishio, Makoto; Takeda, Masayuki; Aoe, Keisuke; Moizumi, Sanae; Nomura, Satoshi; Tajima, Takeshi; Hida, Toyoaki
Abstract: MET mutations leading to exon 14 skipping ( MET Δex14) are strong molecular drivers for non–small‐cell lung cancer (NSCLC). Capmatinib is a highly potent, selective oral MET inhibitor that showed clinically meaningful efficacy and a manageable safety profile in a global phase II study (GEOMETRY mono‐1, NCT02414139) in patients with advanced MET Δex14‐mutated/ MET ‐amplified NSCLC. We report results of preplanned analyses of 45 Japanese patients according to MET status ( MET Δex14‐mutated or MET ‐amplified) and line of therapy (first‐ [1L] or second‐/third‐line [2/3L]). The starting dose was 400 mg twice daily. The primary endpoint was the objective response rate (ORR) assessed by a blinded independent review committee. A key secondary endpoint was duration of response (DOR). Among MET Δex14‐mutated patients, in the 1L group, one patient achieved partial response (DOR of 4.24 months) and the other had stable disease. In the 2/3L group, the ORR was 36.4% (95% confidence interval [CI] 10.9%‐69.2%), median DOR was not evaluable, and progression‐free survival was 4.70 months. One patient (2/3L group) showed partial resolution of brain lesions per independent neuroradiologist review. In MET ‐amplified patients with a MET gene copy number of ≥10, the ORR was 100% (2/2 patients) in the 1L group and 45.5% (5/11 patients) in the 2/3L group, with DOR of 8.2 and 8.3 months, respectively. Common treatment‐related adverse events among the 45 Japanese patients were blood creatinine increased (53.3%), nausea (35.6%), and oedema peripheral (31.1%); most were grade 1/2 severity. In conclusion, capmatinib was effective and well tolerated by Japanese patients with MET Δex14/ MET ‐amplified NSCLC, consistent with the overall population. Abstract : We describe results for Japanese patients enrolled in a global phase II study (GEOMETRY mono‐1, NCT02414139), which investigated the efficacy and safety of capmatinib in patients with advanced non–small‐cell lung cancer (NSCLC) harboring MET exon 14 skipping mutations ( MET Δex14). Capmatinib was effective and well tolerated by Japanese patients. The results are consistent with those observed in the overall population enrolled in GEOMETRY mono‐1.